Analisis Kepuasan Konsumen Terhadap Atribut Sayuran Organik Di Hypermart Manado - Christi M. Tangkulung; Lyndon R.J. Pangemanan; Charles R. Ngangi (COCOS, 2015)
ABSTRACT Formulation of the problem in this research is how the level of customer satisfaction with the attributes of organic vegetables viewed from pricing and product availability, freshness and packing. The purpose of this study was to analyze the level of customer satisfaction with the attributes of organic vegetables viewed from pricing and product availability, freshness and packing. The benefit is to provide information to the company regarding the attributes that need to be considered in improving customer satisfaction with the sales of organic vegetables. Research conducted at Hypermart Manado, where the consumer purchaser of organic vegetables the focus of research, during October 2014 - March 2015. Data collected consist of primary data through direct interviews with consumers and secondary data from information obtained from the company Hyperrmart. 2 Â Sampling method accidental sampling with 40 respondents / consumer as a sample. The data analysis was conducted by the description in the form of a list of tables and figures. The results showed that in terms of price and availability of products, freshness and packaging reached a total score of collecting data in 2022 where the figure measuring consumer satisfaction index amounted to 67.4% and classified satisfied. This shows that consumers of organic vegetables has had a high awareness of the advantages of organic vegetable products. Keywords: Consumer Satisfaction